The Dialectics of Islamic Law: Classical Ijtihad in Addressing Modern Legal Challenges - Rasty Azizah Putri; Hamda Sulfinadia; Sobhan Sobhan; Bakhtiar Bakhtiar (Alhurriyah, 2026)
This research examines the relevance of classical Islamic legal methodology in addressing contemporary legal challenges. Although various studies have discussed the historical development of Islamic legal thought and the contributions of the imams of the schools of thought, studies on the dialectical relationship between classical ijtihad and modern legal issues are still limited. This research aims to analyze the ijtihad methods of Abu Hanifah, Malik ibn Anas, al-Syafi'i, and Ahmad ibn Hanbal and their relevance in the contemporary context. This research uses a qualitative method with a historical-comparative approach through literature review. The results show that classical ijtihad methodology remains dynamic and adaptive. Each imam has his own characteristic methods, such as ra'y and istihsan (Abu Hanifah), ‘amal ahl al-Madinah and maslahah (Malik), systematic qiyas  (al-Syafi'i), and a hadith based approach (Ahmad ibn Hanbal), which provide a flexible basis for legal reasoning. This approach remains relevant in responding to contemporary issues such as Islamic finance, digital technology, artificial intelligence (AI) including automated fatwa systems, and bioethics through a reinterpretation of classical principles. This research confirms the dialectical interaction between classical legal thought and contemporary realities and demonstrates that classical Islamic legal methodology can be reconstructed as a flexible analytical framework.